The application of Foley catheter traction technique in extraperitoneal robot-assisted radical prostatectomy - Xiao-Lu Jiang; Kui OuYang; Rui Yang; Jia-Ning Sun; Feng Zhang; Hong-Wei Zhao (BMC Urology, 2023)
Abstract Objectives To describe a technique to improve exposure of prostate during extraperitoneal robot-assisted radical prostatectomy (EP-RARP). Material and methods From March 2020 to June 2022, a total of 41 patients with prior intra-abdominal surgery underwent EP-RARP. Twenty-three patients improved exposure by traction of prostate through urinary catheter. The catheter traction prostatectomy (CTP) group was compared with the standard prostatectomy (SP) group using three robotic arms (18 patients) in terms of estimated blood loss (EBL), operative time, positive surgical margin rate, the recovery rate of urinary continence, Gleason score and postoperative hospital stays. Differences were considered significant when P < 0.05. Results The operative time was lower in the CTP group (109.63 min vs. 143.20 min; P < 0.001). EBL in the CTP group was 178.26 ± 30.70 mL, and in the standard prostatectomy group, it was 347.78 ± 53.53 mL (P < 0.001). No significant differences with regard to postoperative hospital stay, recovery rate of urinary continence, catheterization time and positive surgical margin were observed between both groups. No intraoperative complications occurred in all the patients. After 6 months of follow-up, the Post-op Detectable prostate specific antigen was similar between the two groups. Conclusion CTP is a feasible, safe, and valid procedure in EP-RARP. Application of CTP improved the exposure of prostate, reduced operative time and blood loss in comparison with the conventional procedure.